2002
DOI: 10.1046/j.1469-0705.2002.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a multiparameter, ultrasound‐based triage on surgical management of adnexal masses

Abstract: The accuracy of this new algorithm was higher than that of the sonographic morphological scoring system alone. In the present series, it allowed the treatment by laparoscopy of 96% of benign adnexal masses without mismanagement of any cases of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…Sonography is considered the firstline imaging technique for discriminating between malignant and benign lesions, and it has been shown to be useful for determining optimal treatment. [1][2][3] In most institutions, a different person from the one who treats the patient and makes clinical decisions performs the sonographic examination. Usually the clinical management decision is based on data provided in the sonographic report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonography is considered the firstline imaging technique for discriminating between malignant and benign lesions, and it has been shown to be useful for determining optimal treatment. [1][2][3] In most institutions, a different person from the one who treats the patient and makes clinical decisions performs the sonographic examination. Usually the clinical management decision is based on data provided in the sonographic report.…”
Section: Discussionmentioning
confidence: 99%
“…When used by experienced examiners, this technique achieves high sensitivity for identifying ovarian cancer, and it has been shown to be useful for selecting the best surgical approach. [1][2][3] However, despite the tremendous progress in the diagnostic capability of TVS, a large multicenter study reported that the false-positive rate could be as high as 24%. 4 One explanation for this high false-positive rate may be operator experience, as has been shown in a recent randomized trial.…”
mentioning
confidence: 99%
“…5 Most studies assessing the role of ultrasound for surgical or referral triaging of adnexal masses have been performed in series in which clinical complaints were not taking into account. [15][16][17][18][19] It could be speculated that the performance of this diagnostic technique could be different in women complaining symptoms suggestive of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6 For these reasons, we think that a "simplified" validated approach based on echo features highly presumptive of a given disease [2][3][4] is not the "simplistic" description of a complex mass advocated by Timor-Tritsch and Goldstein. …”
Section: J Ultrasound Med 2006; 25:558-562mentioning
confidence: 99%
“…Their study does not answer the question of whether a score is more reproducible than the subjective impression because the aim of the study was not to compare the score with other approaches. [2][3][4] Ferrazzi et al 1 stated that their study was designed to assess the intercenter reproducibility of transvaginal gray scale sonographic examination. In our opinion, their study was not designed to assess the reproducibility of the approach because in "Materials and Methods," they did not report any of the several methods to evaluate agreement between observers (eg, the κ index).…”
Section: J Ultrasound Med 2006; 25:558-562mentioning
confidence: 99%